When work–family guilt becomes a women's issue: Internalized gender stereotypes predict high guilt in working mothers but low guilt in working fathers - Aarntzen, Lianne; Derks, Belle; van Steenbergen, Elianne; van der Lippe, Tanja (British Journal of Social Psychology, 2023)
Les stéréotypes de genre prescrivent aux mères, mais pas aux pères, de donner la priorité à leur famille plutôt qu’à leur travail. Par conséquent, l’intériorisation des stéréotypes de genre peut prédire une culpabilité plus élevée chez les mères que chez les pères dans des situations où ils privilégient leur travail plutôt que leur famille. L’étude 1 (135 mères et 116 pères) a en effet révélé que plus les stéréotypes de genre implicites des pères étaient forts (mesurés à l’aide d’une tâche d’association implicite genre-carrière), moins les pères se déclaraient coupables dans une situation fictive d’interférence du travail dans la famille. Bien que les mères aient en moyenne déclaré une culpabilité plus élevée que les pères, cet effet n’a pas été atténué par leurs stéréotypes de genre implicites. L’étude 2 (étude du journal quotidien auprès de 105 mères) a toutefois révélé des preuves de l’effet modérateur des stéréotypes de genre implicites sur la culpabilité des mères qui travaillent. Plus les stéréotypes de genre implicites des mères étaient forts, plus elles déclaraient avoir des conflits entre le travail et la famille et de la culpabilité les jours où elles travaillaient de longues heures. Ces résultats montrent que les stéréotypes de genre implicites façonnent la façon dont les parents perçoivent leurs choix travail-famille.
Keywords: 2000 à aujourd'hui; 2020-2029; care; charge mentale; conciliation famille-travail; culpabilité; discipline; europe; famille; maternité; pays-bas; projet charge mentale; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes de genre; thématiques; travail; émotions

Women's overload during the pandemic: Unpaid care work, financial well-being, and stress - Bulog, Ivana; Pepur, Sandra; Smiljanić, Ana Rimac (Management : Journal of Contemporary Management Issues, 2022)
This study examines the relationship between unpaid care work, financial well-being, and stress levels among women during the COVID-19 pandemic. The pandemic caused downturns in the economies of countries worldwide and led to uncertainties and changes that created conditions for increased stress levels and consequently impaired well-being. In addition to social distancing and lockdown measures to cope with the virus, working from home, home schooling, caring for sick and older family members, and financial problems have added burdens and have proven to be additional personal and family stressors. The findings are based on an online survey conducted among women during the second lockdown in Croatia. Additional unpaid care work and lower financial well-being affect the increased stress felt by women during the pandemic. This is especially pronounced among women who are more involved in paid work. During the pandemic, additional unpaid care work, increased involvement in paid work, and jeopardized financial well-being were stressors for women. Our results indicate the importance of women s free time for their own and their families 'well-being.
Keywords: 2000 à aujourd'hui; 2020-2029; anxiété; care; conciliation famille-travail; covid-19; croatie; discipline; europe; famille; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; sciences de la gestion; thématiques; travail; travail gratuit; économie

“You’re a teacher you’re a mother, you’re a worker”: Gender inequality during COVID‐19 in Ireland - Clark, Serena; McGrane, Amy; Boyle, Neasa; Joksimovic, Natasha; Burke, Lydia; Rock, Nicole; Katriona O’ Sullivan (Gender, Work and Organization, 2021)
The novel coronavirus (COVID‐19) was declared a global pandemic in March 2020. Unlike previous highly contagious diseases that brought the threat of global instability this century such as SARS‐CoV, Zika virus (ZIKV), Swine flu (H1N1), and the Avian flu (H5N1), COVID‐19 was unable to be contained. Global restrictions were implemented to curb the spread of the virus, which included but were not limited to the closure of all educational institutions and the advice to engage in remote working. This study aims to understand the experience of working mothers who managed work and home duties during the COVID‐19 pandemic in Ireland. Thirty working mothers were interviewed in this study, and qualitative analyses were conducted to gain insight into their work and family life during the restrictions. The findings of the analysis indicate that working mothers have been negatively impacted by COVID‐19 in relation to their psychological well‐being, experiences of negative emotions, and the redefinition of family dynamics, in which working mothers have adopted additional and disproportionate care burden. These findings are consistent with the current research arguing that COVID‐19 has highlighted an increase in the gender gap in domestic labor as well as the undermining of career advancement for working mothers.
Keywords: approches et analyses; charge mentale; conciliation famille-travail; division sexuelle du travail; europe; famille; irelande; projet charge mentale; rapports sociaux de sexe; régions géographiques; santé; soins aux enfants; thématiques; travail; travail domestique

« La propriété d’une maison pavillonnaire dans l’imaginaire de la famille et les conditions économiques des familles avec enfants » dans Des imaginaires aux réalités conjugales et familiales: perspectives interdisciplinaires et internationales - Pugliese, Maude (Des imaginaires aux réalités conjugales et familiales: perspectives interdisciplinaires et internationales, 2021)
"La réalisation des projets de couple et familiaux constitue des préoccupations importantes des individus contemporains. Ces projets font l'objet de représentations sociales générées par diverses sources?: œuvres littéraires, philosophiques, scientifiques, populaires, mais aussi cinématographiques ou médiatiques. Ces représentations proposent des modèles et fournissent des supports à des imaginaires alimentant les scénarios personnels, créant des attentes qui se heurtent aux réalités quotidiennes, et qui entrainent souvent des désillusions et des déceptions, mais aussi des adaptations. Dans le but de mieux saisir les logiques à l'œuvre dans les attentes conjugales et familiales, cet ouvrage composé de treize chapitres rédigés par des chercheuses et chercheurs québécois, canadiens et internationaux (Brésil, Espagne, France, Suisse), issus de disciplines variées (anthropologie, démographie, psychologie, sexologie, sociologie et travail social), vise à mettre en évidence l'influence des imaginaires sur les itinéraires conjugaux et familiaux. La richesse des contributions à cet ouvrage collectif devrait aider à mieux saisir l'importance des études sur les imaginaires familiaux, autant pour la communauté scientifique que pour toute personne intéressée à mieux comprendre, et possiblement à mieux accompagner, les imaginaires, les attentes et les désillusions conjugales et familiales vécues par les individus et les couples."
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; europe; famille; inégalités; maternité; patriarcat; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques

Still a superwoman? How female academics from the former Soviet Union negotiate work-family balance abroad - Antoshchuk, Irina A; Gevinner, Irina (Monitoring Obshchestvennogo Mneniya: Ekonomicheskie i Sotsial'nye Peremeny, 2020)
Since the 1930s, a peculiar 'working mother' gender contract was dominant in the Soviet Union formally empowering women. The pressing expectation of this contract and a necessity to combine motherhood, housework and employment led to the image of the near superwoman who 'has it all'. This paper examines whether highly-skilled Russian-speaking female academics continue to adhere to this cultural ideal striving for work-life balance after migration to the UK and Germany. Based on qualitative interviews with 22 female scholars, the article provides a typology of scenarios for negotiating professional and private life. It elaborates on how role-related partners contribute to achieving balance between paid employment and mothering and explores the consequences for women's well-being. Moreover, the study suggests a feminist approach to analyzing work-family balance, which valorises women's point of view, emphasizing motherhood, children and family relations as an essential personal and social value, while also documenting the increasing challenges faced in the realization of these life priorities. © 2020 Russian Public Opinion Research Center, VCIOM. All rights reserved.
Keywords: 2000 à aujourd'hui; 2010-2019; allemagne; asie; charge mentale; conciliation famille-travail; discipline; europe; ex-URSS; famille; femmes* russophones; projet charge mentale; périodes historiques; ressource en ligne; royaume-uni; russie; régions géographiques; sciences humaines; sociologie; thématiques; travail

Capturing conflicting accounts of domestic labour: The household portrait as a methodology - Christopher, Emily (Sociological Research Online, 2020)
Drawing on data from a UK study conducted in 2014/2015, based on qualitative interviews with 25 working parent, heterosexual couples on their domestic division of labour, I argue that the interactive methodology of the ‘Household Portrait’ not only provides data on the distribution of household labour but also reveals gender differences in how domestic labour is conceptualised and measured. Disagreements and inconsistencies between couples over who ‘mostly’ does various tasks embody gendered perceptions of the meaning of doing domestic tasks and the appropriate temporal frame for evaluating individual contributions. Partners’ joking competition over their respective contributions highlight not just the normative expectations guiding what women and men feel they should do but also the criteria that they think should be used to measure their contributions. © The Author(s) 2020.
Keywords: approches et analyses; charge mentale; couple hétérosexuel; discipline; europe; famille; projet charge mentale; royaume-uni; régions géographiques; répartition des tâches domestiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

Le « parent hélicoptère » et le paradoxe de la parentalité intensive au XXIe siècle - Ellie Lee; Jan Macvarish (Lien Social et Politiques, 2020)
Le terme « parent hélicoptère » est aujourd’hui très présent dans les discours public et professionnel sur l’éducation des enfants, ainsi que dans la culture de façon plus générale, particulièrement en Amérique du Nord et au Royaume-Uni. Un petit nombre de travaux sociologiques ont mis en évidence le caractère paradoxal de ce phénomène, qui réside dans une inquiétude souvent exagérée envers l’investissement « excessif » de ces parents dits « hélicoptères » auprès de leurs enfants, au sein même d’une culture de la parentalité intensive. Cet article développe ces travaux de deux manières. Nous resituons d’abord l’utilisation désormais omniprésente du terme « parent hélicoptère » et les qualificatifs qui y sont associés en examinant ses antécédents discursifs dans la terminologie du XXe siècle — comme l’overparenting (surparentalité), le smothering (parent poule ou parent qui couve) ou le coddling (dorlotement) — et en soulignant leur coexistence avec les récits de « mauvaises mères », considérées comme distantes et non impliquées. Ensuite, en analysant l’utilisation du terme helicopter parent faite dans les médias britanniques depuis la fin du XXe siècle, nous analysons comment se construisent les préoccupations actuelles concernant le surinvestissement des parents dans l’éducation de leurs enfants. Nous avons observé que les thèmes les plus récurrents de la couverture médiatique concernaient l’amour parental qui a mal tourné (gone wrong), la pression parentale (parental pushiness), ainsi que la classe sociale du parent hélicoptère. Notre analyse suggère que l’expression « parent hélicoptère » peut être mieux comprise comme un aspect du langage vernaculaire du XXIe siècle qui exprime une certaine aversion envers les résultats perçus d’une parentalité intensive, mais qui laisse intactes les prémisses concernant la responsabilité parentale en matière de pathologies individuelles et sociales. Nous concluons que, pour les sociologues, une caractéristique importante du parent hélicoptère est qu’il est généralement perçu comme un parent « à problèmes » issu de la classe moyenne, et nous suggérons que cette construction de l’origine sociale des défaillances parentales est une question importante à prendre en considération à l’avenir dans les études sur la culture de la parentalité.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; angleterre; approches et analyses; cours; discipline; europe; famille; maternité; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2264; sociologie; thématiques; états-unis

The care ceiling in higher education - Lynch, Kathleen; Ivancheva, Mariya; O'Flynn, Micheál; Keating, Kathryn; O'Connor, Monica (Irish Educational Studies, 2020)
This study examines the impact of managerialist policies on care relations in higher education. It is based on a study of 10 higher education institutions in Ireland. The paper shows that a care-free worker model is ingrained in systems of performance appraisal, especially for academics in universities, and increasingly in the Institutes of Technology, although it also impacts on support staff in other professions and occupations. It assumes a life of boundary-less working hours and unhindered mobility. The market-informed tools of performance appraisal, especially audits and metrics, cannot measure essential care work because care is a process and disposition, not a product. Because it is not countable caring becomes invisible as do the people who do it. The managerial ideology of 'work--life balance' merely operates as a mask that conceals how over-working is normalised. There is no legitimate language to name over-working for the structural problem that it is. When work organisations disregard care commitments outside of work, and even within it, these are then repackaged and fed back to women/carers as personal problems and failures. The idealised care-free worker model operates as a care ceiling over women particularly; it is taken as given, even natural.
Keywords: 2000 à aujourd'hui; approches et analyses; care; charge mentale; conciliation famille-travail; europe; famille; femmes universitaires*; irlande; patriarcat; politiques néolibérales; projet charge mentale; périodes historiques; rapports sociaux de sexe; rentabilité; régions géographiques; systèmes d'oppressions; thématiques; travail; travail du care